Innovative Approaches to Regenerate Enamel and Dentin - Xanthippi Chatzistavrou; Silvana Papagerakis; Peter X. Ma; Petros Papagerakis (International Journal of Dentistry)
The process of tooth mineralization and the role of molecular control of cellular behavior during embryonic tooth development have attracted much attention the last few years. The knowledge gained from the research in these fields has improved the general understanding about the formation of dental tissues and the entire tooth and set the basis for teeth regeneration. Tissue engineering using scaffold and cell aggregate methods has been considered to produce bioengineered dental tissues, while dental stem/progenitor cells, which can differentiate into dental cell lineages, have been also introduced into the field of tooth mineralization and regeneration. Some of the main strategies for making enamel, dentin, and complex tooth-like structures are presented in this paper. However, there are still significant barriers that obstruct such strategies to move into the regular clinic practice, and these should be overcome in order to have the regenerative dentistry as the important mean that can treat the consequences of tooth-related diseases.